2022
DOI: 10.1108/qrfm-01-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Governing Fintech for sustainable development: evidence from Italian banking system

Abstract: Purpose Customer satisfaction has been traditionally the main goal aimed at by managers. Focusing on the banking industry, the importance of this concept is even greater because of the increasing focus of banks on mobile services to reach out to a larger set of customers. To investigate user’s behavior in a Fintech context, this study aim to focus on two relevant issues: service quality and perceived risk. For the purpose, the authors integrated a technology quality-based model with a green image perspective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…From an empirical point of view, Campanella et al [57] observed the importance that Fintech providers have a green reputation since it enhances the consumers' trust and satisfaction with the offered internet banking services. These scholars encourage the financial institutions to promote sustainable development and green strategies in their planning as concern for the environment and sustainability affects consumers, who increasingly consider non-financial attributes in their investments, such as environmental, social, and governance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…From an empirical point of view, Campanella et al [57] observed the importance that Fintech providers have a green reputation since it enhances the consumers' trust and satisfaction with the offered internet banking services. These scholars encourage the financial institutions to promote sustainable development and green strategies in their planning as concern for the environment and sustainability affects consumers, who increasingly consider non-financial attributes in their investments, such as environmental, social, and governance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…So, traditional banks are starting to see a reduction in their share of the market [7]. The growth of financial technology has a substantial impact on banks since many banking products are informationbased [8][9][10][11]. On the other hand, contemporary ITs and data analysis techniques enable the digital personalization of many financial services [12].…”
Section: Reviews Of Literaturementioning
confidence: 99%
“…Pengguna akan semakin loyal bila Fintech dapat mengamankan data-data pribadi dari pemilik akun yang telah mendaftar sejak awal (Campanella et al, 2022).…”
Section: Fenomena Mengenai Fintech Pada Saat Ini Adalah Tersedianya B...unclassified
“…Pemanfaatan Fintech yang berulang dan berkelanjutan tidak hanya penting untuk membangun komitmen dan kepuasan, tetapi juga penting untuk mengamankan pengembalian investasi di Fintech. Oleh karena itu, kepuasan pengguna perlu mendapat perhatian lebih karena berdampak pada masa depan perusahaan Fintech yaitu semakin baik pengelolaan keamanan data maka semakin meningkat kepuasan pelanggan (Campanella et al, 2022;Cao et al, 2021).…”
Section: Fenomena Mengenai Fintech Pada Saat Ini Adalah Tersedianya B...unclassified